2021
DOI: 10.1111/jipb.13146
|View full text |Cite
|
Sign up to set email alerts
|

Development of an efficient plant dual cytosine and adenine editor

Abstract: Summary An enhanced CDA‐like (eCDAL) was established from Japanese lamprey CDA1‐like 4 to achieve a high editing frequency in a broad region as a C‐terminal cytosine base editors (CT‐CBE). Then, a novel plant dual‐base editor version 1(pDuBE1) was developed by integrating TadA‐8e into eCDAL. The editing efficiency of pDuBE1 could reach to 87.6%, with frequencies of concurrent A‐to‐G and C‐to‐T conversions as high as 49.7% in stably transformed plant cells. Our results showed that pDuBE1 could mediate robust du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The development of the base editing technology resulted in improvements in the CBEs [ 115 , 116 , 117 , 118 , 119 ] and ABEs [ 120 , 121 ] characteristics, such as reduced off-target activity, indel frequency, and nCas9 expression levels. Recently, double base editors with CD and AD activities were also developed, first for mammalian cells [ 122 , 123 , 124 , 125 ], and then for plants [ 126 , 127 ].…”
Section: Editing the Plant Genome In Transgenic Hairy Roots: Vector Componentsmentioning
confidence: 99%
“…The development of the base editing technology resulted in improvements in the CBEs [ 115 , 116 , 117 , 118 , 119 ] and ABEs [ 120 , 121 ] characteristics, such as reduced off-target activity, indel frequency, and nCas9 expression levels. Recently, double base editors with CD and AD activities were also developed, first for mammalian cells [ 122 , 123 , 124 , 125 ], and then for plants [ 126 , 127 ].…”
Section: Editing the Plant Genome In Transgenic Hairy Roots: Vector Componentsmentioning
confidence: 99%
“…Cytosine and adenosine base editors (CBE and ABE) have been vigorously developed in plants, but the base conversion types are limited (Ren et al, 2018(Ren et al, , 2021Xu et al, 2021). A new base editor CGBE with a uracil DNA N-glycosylase (UNG) has recently been reported that enables efficient C-to-G editing in mammalian cells (Kurt et al, 2021).…”
mentioning
confidence: 99%
“…Various cytidine deaminases have been tested to diversify CBEs, including mammalian APOBEC family proteins such as AID [65][66][67][68], APOBEC1 and APOBEC3 (A3A-H) proteins [69][70][71][72][73][74], and lamprey-derived CDA1 family proteins such as CDA1 [29,63,64,[75][76][77]. Simultaneous incorporation of multiple (identical or different) deaminase domains into a BE fusion protein broadens the accessibility of substrate nucleotides in the R-loop, thus widening the base editing window [78], diversifying editing reactions (i.e., by combining a cytidine deaminase domain with an adenosine deaminase domain) and/or increasing editing efficiency [79][80][81][82][83]. Cytidine deaminases also exhibit certain preferences related to the sequence composition of their substrate nucleic acid, which can further influence the width of the activity window of CBEs, but also their activity on different targets.…”
Section: Engineering Bes For Altered Activity Windowsmentioning
confidence: 99%